Functional mixed cobalt and aluminum oxide coatings for environmental safety - Ved, M.V.; Sakhnenko, N.D.; Karakurkchi, A.V.; Myrna, T.Yu. (Functional Materials, 2017)
Principles of plasma-electrolytic oxidation of the aluminum alloys in diphosphate electrolytes are discussed. It has been established that a variation in concentration of the electrolyte components and electrolysis parameters (current density and treatment time) provides the formation of oxide coatings consisting of the basic matrix materials and the cobalt oxides of different composition and morphology that are expected to affect their functional properties. Mixed oxide coatings formed in a plasma-electrolytic mode characterized by microglobular structure with reducing the conglomerate size have an increased abrasion and wear resistance and an intense catalytic activity. Thus, there is a prospect of using such coatings in the process of burning fuel in internal combustion engines and reduce the toxicity of emissions improving fuel efficiency and environmental performance of engines and in the industrial systems of catalytic purification of exhaust gases of industrial plants and power system facilities.